Meta-APL: a general language for agent programming - Doan, Thu Trang (2014)
A key advantage of BDI-based agent programming is that agents can deliberate about which course of action to adopt to achieve a goal or respond to an event. However while state-of-the-art BDI-based agent programming languages provide flexible support for expressing plans, they are typically limited to a single, hard-coded, deliberation strategy(perhaps with some parameterisation) for all task environments. In this thesis, we describe a novel agent programming language, meta-APL, that allows both agent programs and the agent’s deliberation strategy to be encoded in the same programming language. Key steps in the execution cycle of meta-APL are reflected in the state of the agent and can be queried and updated by meta-APL rules, allowing a wide range of BDI deliberation strategies to be programmed. We give the syntax and the operational semantics of meta-APL, focussing on the connections between the agent’s state and its implementation. Finally, to illustrate the flexibility of meta-APL, we show how Jason and 3APL programs and deliberation strategy can be translated into meta-APL to give equivalent behaviour under weak bisimulation equivalence.